Is there a single beta oscillation band interfering with movement in Parkinson's disease?. (13th May 2021) - Belova, Elena M.; Semenova, Ulia; Gamaleya, Anna A.; Tomskiy, Alexey A.; Sedov, Alexey
Abstract: Beta oscillations in basal ganglia are considered to contribute to motor dysfunction in Parkinson's disease (PD). However, there is a high variety in frequency borders for beta oscillations between studies, which complicates the comparison and interpretation of results. Here we aimed to study the homogeneity of oscillations in the broad "beta" range (8–30 Hz) and their implication to motor functioning in PD. For this purpose, we recorded local field potentials (LFP) in the subthalamic nucleus (STN) during 34 deep brain stimulation surgeries. We identified spectral features of LFP recordings in the range 8–30 Hz to search for candidate sub‐regions of stable oscillations and assessed their association with clinical scores on the contralateral side of the body and sensitivity to motor tests. Lower frequency oscillations (8–16 Hz) had a significant positive association with bradykinesia score. During voluntary movements, we observed a significant increase in LFP power in the 12–16 Hz range and a decrease in the 18–26 Hz range. We may conclude that the 8–30 Hz oscillation range includes oscillations with different functional features—sensitivity and responsiveness to movement, and clinical symptoms, which should be taken into account in further studies of beta oscillations association with PD pathophysiology. These data assume the coexistence of several frequency domains within beta range that are modulated in different ways under dopaminergic regulation and motor processing in human STN. Abstract : Beta oscillations in STN‐LFPs are thought to contribute to motor impairment in PD. However, there may be several oscillation ranges within the beta band. Using a sliding window approach, we have examined this issue. Association with PD motor signs was significant only for lower beta band: Namely, bradykinesia was associated with LFP power in 8–16 Hz range. At the same time, we observed opposite changes in beta power during hand movements—an increase in 12–16 Hz and a decrease in 18–26 Hz range.